A submarine canyon as a climate archive — Interaction of the Antarctic Intermediate Water with the Mar del Plata Canyon (Southwest Atlantic) - Voigt, Ines (2013)
The Mar del Plata Canyon is located at the continental margin off northern Argentina in a key intermediate and deep-water oceanographic setting. In this region, strong contour currents shape the continental margin by eroding, transporting and depositing sediments. These currents generate various depositional and erosive features which together are described as a Contourite Depositional System (CDS). The Mar del Plata Canyon intersects the CDS, and does not have any obvious connection to the shelf or to an onshore sediment source. Here we present the sedimentary processes that act in the canyon and show that continuous Holocene sedimentation is related to intermediate-water current activity. The Holocene deposits in the canyon are strongly bioturbated and consist mainly of the terrigenous ?sortable silt? fraction (10?63 μm) without primary structures, similarly to drift deposits. We propose that the Mar del Plata Canyon interacts with an intermediate-depth nepheloid layer generated by the northward-flowing Antarctic Intermediate Water (AAIW). This interaction results in rapid and continuous deposition of coarse silt sediments inside the canyon with an average sedimentation rate of 160 cm/kyr during the Holocene. We conclude that the presence of the Mar del Plata Canyon decreases the transport capacity of AAIW, in particular of its deepest portion that is associated with the nepheloid layer, which in turn generates a change in the contourite deposition pattern around the canyon. Since sedimentation processes in the Mar del Plata Canyon indicate a response to changes of AAIW contour-current strength related to Late Glacial/Holocene variability, the sediments deposited within the canyon are a great climate archive for paleoceanographic reconstructions. Moreover, an additional involvement of (hemi) pelagic sediments indicate episodic productivity events in response to changes in upper ocean circulation possibly associated with Holocene changes in intensity of El Niño/Southern Oscillation.